High-piezoelectric lead-free BiFeO3BaTiO3 ceramics with enhanced temperature stability and mechanical properties - Xiaoxiao Zhou; Yuxin Xu; Xiaoqi Gao; Chengchao Hu; Wan Jiang; Hezhang Li; Bo-Ping Zhang (Journal of Materiomics)
BiFeO3BaTiO3 (BF–BT) ceramics exhibit higher piezoelectric coefficients (d33), Curie temperatures (TC), and temperature stability than other high-temperature lead-free piezoelectric materials. However, despite their crucial role in piezoelectric devices, the mechanical properties of BF–BT ceramics have been underexplored. A thorough evaluation of the mechanical properties of BF–BT is crucial for developing cost-effective and durable lead-free piezoelectric ceramics. Moreover, the specific causes of the high piezoelectric response and excellent temperature stability of BF–BT ceramics remain unclear owing to the instrumental detection threshold, which limits experimental studies to temperatures above 140 °C and below the degradation temperature of d33. To investigate the intrinsic origins of the high piezoelectricity and temperature stability of BF–xBT ceramics and to enhance their mechanical properties, a two-step sintering process is used to fabricate these ceramics (0.25 ≤ x ≤ 0.40). Owing to improvements in grain refinement and reduced Bi3+ volatilization, the BF–0.33 BT ceramic exhibits enhanced overall performance, with a modified small punch strength of 155 MPa, Vickers hardness of 5.2 GPa, a d33 of 220 pC/N at room temperature, TC of 466 °C, and d33 values exceeding 400 pC/N at 260 °C. Phase-field simulations, which address the limitations of device detection thresholds, reveal that with increasing temperature, the domain structure relaxes, and polarization intensity decreases. This indicates that changes in the high-temperature piezoelectric properties can be attributed to domain structure relaxation and the increase in dielectric constant. Overall, BF–BT ceramics exhibit superior piezoelectric performance, mechanical properties, and temperature stability, making them highly suitable for use in high-temperature and demanding environments.